Pediatric Splenic Injuries - Dr. Mohd. Altaf Mir; Prince Kumar (Pediatric Abdominopelvic Trauma, 2024)
This chapter comprehensively explores the multifaceted landscape of pediatric splenic trauma, encompassing crucial facets from anatomy and physiology to etiology, clinical presentation, and contemporary grading systems. Beginning with an in-depth examination of the unique anatomical and physiological features of the pediatric spleen, the narrative unfolds to elucidate the diverse causes of splenic trauma and the clinical manifestations that characterize this condition in children. The discussion navigates through the American Association for the Surgery of Trauma (AAST) and the World Society of Emergency Surgery (WSES) grading systems, offering a structured understanding of the severity of splenic injuries. Insightful perspectives on diagnosis unveil the evolving landscape of imaging modalities and clinical assessments, ensuring a nuanced approach to identifying and classifying splenic trauma in pediatric patients. The core of this chapter delves into the intricacies of management strategies, addressing both non-operative and operative approaches with a keen emphasis on splenic preservation whenever viable. From non-operative measures to surgical interventions, the chapter provides a comprehensive guide for clinicians navigating the complex terrain of pediatric splenic trauma. As the narrative unfolds, attention is devoted to the spectrum of complications that may arise in the aftermath of splenic trauma, ranging from early to delayed sequelae. The abstract encapsulates a wealth of knowledge, offering clinicians and researchers a valuable resource for understanding, diagnosing, and managing pediatric splenic trauma, ultimately contributing to enhanced patient care and outcomes.